A Prototype of a millet planting machine for Jigawa State, Nigeria - Dauda, Abdulrauf Baba
Farming is the occupation of most of the rural dwellers, in Nigeria, more than half of the populace are farmers. Most of these farmers use traditional methods of farming which is time-consuming, and numerous skilled workers would be required to farm a large area of land. The planting procedure is as follows: - The farm is cleared by removing roots, sticks and all unwanted debris, shrubs and burnt. - Harrowing then follows (some do not harrow their farm). - Then ridges is then prepared on the farm, some uses tractors, bulls or it is manual method. The holes are then dug on the ridges using a long hoe ( distance between holes is not measure ). - The seeds are then planted and covered with sand using feet. The number of seed is not metered; these just poured into the hole and covered with sand. After germination, some of the seedlings are removed, leading to wastage of seeds during planting. These discarded seeds could be saved, used for planting in other farms or sold to earn extra income. These could be addressed by designing and constructing a planting machine where by the number of seeds planted per hole is controlled, the distance between stalks is also calculated and correctly planted. In the end no removal of any excess seedling is done, and the digging and planting is done simultaneously at a faster time compared with the traditional method where they are done differently. The planting machine was tested on a ridges of 820 cm in length. 5 -6 millet seeds were dispensed per hole on the ridges and covered in 1 min 25 secs, no removal of excess seed, and more stands would be cultivated compared with the manual method.